Meningkatkan kepuasan pelanggan dan kualitas layanan Kedai Kebab dan Burger - Kumala, Alfaina Dica Putri (Maliki Interdisciplinary Journal, 2024)
This study discusses what food stalls can do to improve customer satisfaction and service quality. The research method used was direct observation of the research object, namely the Dau Kebab and Burger Food Stalls, Malang Regency. Research findings suggest that increasing seating, improving stock management of essential ingredients such as cheese, and training employees in communicating and accurately recording customer orders can improve service. It is hoped that this shop can achieve a higher level of customer satisfaction, improve the company’s image, and build longer relationships with customers through implementing these solutions.